Cerebral adaptations to chronic anemia in a model of erythropoietin-deficient mice exposed to hypoxia - El Hasnaoui-Saadani, Raja; Pichon, Aurélien; Marchant, Dominique; Olivier, Paul; Launay, Thierry; Quidu, Patricia; Beaudry, Michèle; Duvallet, Alain; Richalet, Jean-Paul; Favret, Fabrice (American journal of physiology. Regulatory, integrative and comparative physiology, 2009)
Anemia and hypoxia in rats result in an increase in factors potentially involved in cerebral angiogenesis. Therefore, the aim of this study was to assess the effect of chronic anemia and/or chronic hypoxia on cerebral cellular responses and angiogenesis in wild-type and anemic transgenic mice. These studies were done in erythropoietin-deficient mice (Epo-TAg(h)) in normoxia and following acute (one day) and chronic (14 days, barometric pressure = 420 mmHg) hypoxia. In normoxia, Epo-TAg(h) mice showed an increase in transcript and protein levels of hypoxia-inducible factor 1alpha (HIF-1alpha), vascular endothelial growth factor (VEGF), erythropoietin receptors (EpoR), phospho-STAT-5/STAT-5 ratio, and neuronal neuronal nitric oxide synthase (nNOS) along with a higher cerebral capillary density. In wild-type (WT) mice, acute hypoxia increased all of the studied factors, while in chronic hypoxia, HIF-1alpha, EpoR, phospho-STAT-5/STAT-5 ratio, nNOS, and inducible NOS remained elevated, with an increase in capillary density. Surprisingly, in Epo-TAg(h) mice, chronic hypoxia did not further increase any factor except the nitric oxide metabolites, while HIF-1alpha, EpoR, and phospho-STAT-5/STAT-5 ratio were reduced. Normoxic Epo-TAg(h) mice developed cerebral angiogenesis through the HIF-1alpha/VEGF pathway. In acute hypoxia, WT mice up-regulated all of the studied factors, including cerebral NO. Polycythemia and angiogenesis occurred with acclimatization to chronic hypoxia only in WT mice. In Epo-TAg(h), the decrease in HIF-1alpha, VEGF proteins, and phospho-STAT-5 ratio in chronic hypoxia suggest that neuroprotective and angiogenesis pathways are altered.